The government of childhood: A systematic analysis of the study of public policies aimed at children under the protection of the State - Morales Retamal, Camilo (Journal Studies of Public Policy, 2022)
The objective of this article is to present a review of the literature on the development of knowledge, based on social sciences, in the field of public policies for children under the protection of the Estate obtained from research conducted in Chile, Argentina, Brazil, Uruguay, and Colombia between 2012 and 2021. Its purpose is to characterize and analyze how protection policies construct their object of intervention and the conjectures from which they orient their actions. A total of 41 texts were analyzed according to the guidelines and procedures for a systematic review, with the objective of ensuring the development of a transparent, clear, and precise text. The thematic content analysis was used to carry out the process of analyzing the documents. The results show that the field of knowledge production on specialized protection is composed of a plurality of theoretical and methodological approaches, indicating that childhood is a social and historical construct that is in constant dispute. Public policies for children are not reduced to just the mechanical application of a set of actions to solve social problems, but rather they are complex discursive constructions that have effects of truth and power in shaping contemporary childhood protection.